What Does It Mean to Be an Activist Scholar? Re‐Imagining Our Responses as Anthropologists of Education to Contemporary Challenges. (September 2014) - Schultz, Katherine
<x xml:space="preserve">Abstract</x> In this address, I ask: What do we bring as anthropologists and educators to our work? Two projects frame my arguments: my work with teachers in Aceh, Indonesia after the 2004 tsunami and my term on a school board in an impoverished U.S. city. I conclude that at a time when challenges are simultaneously local and global, immediate and long term, we must draw from both fields while working for sustainable change and a more just world.